Code-switching Practices at EnglishTeacher Education Program in Multilingual Indonesian Society - Imelwaty, Sri (Kopertis Wilayah X (Sumbar, Riau, Jambi, dan Riau Kepulauan), 2016)
Code-switching is becoming a common phenomenon which occur extensively in English teachers’ speech in the classrooms where English is not the first language of both teachers and students. In the Indonesian context, particularly where a regional language is used along with the national language (Bahasa Indonesia) both teachers and students are able to speak more than one language. However, many second and foreign-language educators and researchers have developed strong beliefs about using code-switching in teaching English is not an effective way to help students mastering English language. One of the views claims that code switching is a sign of an inability to express oneself, and it reduces the opportunity of using English completely. For this reason, English teachers use of code-switching is regarded as a factor leading to the decline of English language proficiency, despite of the fact that these beliefs may not always grounded in theory or research. This project has aim to describe the application of code-switching practices among the English teachers at English education program in West Sumatra Indonesia where people commonly used Bahasa Indonesia and their regional language i.e. Minangkabau language in communication.The findings of the study show that both intrasentential and intersentential switching are applied by those English teachers